Yearling Cattle Grazing Pastures Burned During Summer Perform Similarly to Cattle Grazing Pastures Burned in Early Spring: Year 2 of 6 - Z. M. Duncan; A. J. Tajchman; M. P. Ramirez; J. Lemmon; W. R. Hollenbeck; D. A. Blasi; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective was to evaluate the impact of prescribed fire timing on grazing performance of yearling beef cattle in the Kansas Flint Hills. Study Description:This study was conducted at the Kansas State University Beef Stocker Unit. Yearling stocker cattle were assigned randomly to one of three prescribed-burn treatments: spring (April 7 ± 2.1 days), summer (August 21 ± 5.7 days), or fall (October 2 ± 9.9 days) and grazed from May to August of 2019 and 2020. Individual body weights were recorded at the beginning and end of the grazing season to determine total body weight gain and average daily gain. The Bottom Line:The first two years of data from a 6-year study were interpreted to indicate that yearling cattle grazing pastures burned in summer performed similarly to those grazing pastures burned in spring.
Keywords: grazing; prescribed fire; sericea lespedeza